THE EFFECT OF STORY TELLING METHOD ON STUDENTS’ VOCABULARY MASTERY AT THE ELEVENTH GRADE OF SMA NEGERI 1 KOLANG IN 2021/2022 ACADEMIC YEAR - Relgy Tio Findy Simatupang (JURNAL LINER (Language Intelligence and Educational Research), 2022)
ABSTRACT: The purposes of this research are to find out: 1) the extent of using story telling method in teaching vocabulary at the eleventh grade students of SMA Negeri 1 Kolang in 2021/2022 academic year. 2) the extent of the students’ vocabulary mastery before and after using story telling method on students’ vocabulary mastery at the eleventh grade students of SMA Negeri 1 Kolang in 2021/2022 Academic Year. 3) whether there is a significant effect of using story telling method on students’ vocabulary mastery at the eleventh grade students of SMA Negeri 1 Kolang in 2021/2022 Academic Year. The population of this research were all the eleventh grade students of SMA Negeri 1 Kolang is 136 students. The research sample was the eleventh IPA 2 students, which consist of 33 students who were taken by purposive sampling. The data collection technique used the observation sheet and test. The results of this research: 1) The use of story telling method is 3.58, it is categorized “very good” criterion. 2) The mean score of the students’ vocabulary mastery before using story telling method is 40.36, it is categorized “fail”. Meanwhile, after using story telling method was 81.15 it was categorized “very good”. 3) the results of data analysis showed that the ttest is higher than ttable (ttest 40.36 > ttable 2.03). So, the hypothesis was accepted. It means that there is a significant effect of story telling method on students’ vocabulary mastery at the eleventh grade of SMA Negeri 1 Kolang in 2021/2022 academic year. Keywords: Story Telling Method, Vocabulary Mastery ABSTRAK: Tujuan penelitian ini adalah untuk mengetahui: 1). Bagaimanakah penggunaan metode bercerita dalam pengajaran kosa kata pada siswa kelas sebelas SMA Negeri 1 Kolang Tahun Pelajaran 2021/2022. 2). Sejauh mana penguasaan kosa kata siswa sebelum dan sesudah menggunakan matode bercerita terhadap penguasaan kosa kata siswa pada kelas XI SMA Negeri 1 Kolang Tahun Pelajaran 2021/2022. 3). Apakah ada pengaruh yang signifikan penggunaan metode bercerita terhadap penguasaan kosa kata siswa pada siswa kelas XI SMA Negeri 1 Kolang Tahun Pelajaran 2021/2022. Populasi dalam penelitian ini adalah seluruh kelas XI SMA Negeri 1 Kolang yaitu 136 siswa. Sampel penelitian ini adalah siswa kelas XI IPA 2 yang berjumlah 33 siswa yang diambil secara purposif. Teknik pengumpulan data menggunakan lembar observasi dan tes. Hasil penelitian ini: 1) Penerapan metode bercerita adalah 3.58, termasuk kriteria “sangat baik”. 2) Rata rata skor penguasaan kosa kata siswa sebelum menggunakan metode bercerita adalah 40.36 dikategorikan “gagal”. Sedangkan setelah menggunakan metode bercerita adalah 81.15 dikategorikan “sangat baik”. 3) hasil analisis data menunjukkan bahwa thitung lebih besar dari ttabel (thitung 40.36 > ttabel 2.03). Jadi, hipotesis diterima. Artinya ada pengaruh yang signifikan pada metode bercerita terhadap penguasaan kosa kata siswa pada siswa kelas XI SMA Negeri 1 Kolang tahun ajaran 2021/2022. Kata Kunci: Metode bercerita, Penguasaan kosa kata